Legal Implications On Credit Agreements For Couple And Wife In Marriage Agreements After Marriage - Adessya Thalia Chairunissa; Liza Priandhini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
A marriage that is legally carried out by husband and wife will have legal consequences for both parties that have an impact on the legal relationship between the two, including property in marriage. In this case, the Civil Code and the Marriage Law recognize the concept of "Marriage Agreements" to regulate the management and use of assets in marriage, whether they are inherited or joint assets. A marriage agreement made by a husband and wife is binding on both parties who made it and will apply to a third party as long as the party is involved. The problem in this study is how the legal implications of post-marital marriage agreements affect credit agreements made by married couples and the legal consequences of post-marital credit agreements on guarantees given by husband and wife to the bank. Based on this research, it can be concluded that: (1) The legal implications of post-marital marriage agreements on credit agreements made by married couples depend on the registration of the marriage agreement. If the marriage agreement is not registered, it will not affect the credit agreement. However, if the agreement is registered, it will have a significant impact on the legal standing of the debtor, the certainty of debt guarantees, and legal protection for the bank. In essence, the debtor cannot be written off in a credit agreement solely because a marriage agreement is made. (2) If a husband and wife bind themselves in a credit agreement, the guarantee provided can be in the form of joint assets they have. If the assets are still insufficient to pay off the debt, the bank can take legal action in the form of Actio Paulina.